STUDENTS’ RESPONSES TOWARD THE IMPLEMENTATION OF GENRE BASED APPROACH THROUGH INSTAGRAM POSTS - Putri Alika Adelia; Yanuarti Apsari (PROJECT (Professional Journal of English Education), 2022)
This study aims to describe students' responses toward the implementation of Genre Based Approach through instagram posts in teaching wriitng. This study used descriptive qualitative methods. The participants of the study were 39 students of Vocational High School in Cimahi. The data were taken through questionnaire. The result of this study showed that students gave positive response toward the implementation of teaching writing using Genre Based Approach through instagram posts. The data revealed that all respondents (100%) motivated to get better grades. In addition, most of students (94.4%) stated that learning using Genre Based Approach are interesting and make them courageous in expressing their opinion. Furthermore, most of students (83.3%) also agreed that Genre Based Approach through instagram posts made it easier to understand the material.  Keywords:  Writing, Genre Based Approach, Instagram Posts